The Selective Angiotensin II Type 2 Receptor Agonist, Compound 21, Attenuates the Progression of Lung Fibrosis and Pulmonary Hypertension in an Experimental Model of Bleomycin-Induced Lung Injury - Rathinasabapathy, Anandharajan; Horowitz, Alana; Horton, Kelsey; Kumar, Ashok; Gladson, Santhi; Unger, Thomas; Martinez, Diana; Bedse, Gaurav; West, James; Raizada, Mohan K.; Steckelings, Ulrike M.; Sumners, Colin; et al. (Frontiers in Physiology, 2018)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic lung disease characterized by scar formation and respiratory insufficiency, which progressively leads to death. Pulmonary hypertension (PH) is a common complication of IPF that negatively impacts clinical outcomes, and has been classified as Group III PH. Despite scientific advances, the dismal prognosis of IPF and associated PH remains unchanged, necessitating the search for novel therapeutic strategies. Accumulating evidence suggests that stimulation of the angiotensin II type 2 (AT2) receptor confers protection against a host of diseases. In this study, we investigated the therapeutic potential of Compound 21 (C21), a selective AT2 receptor agonist in the bleomycin model of lung injury. A single intra-tracheal administration of bleomycin (2.5 mg/kg) to eight-week old male Sprague Dawley rats resulted in lung fibrosis and PH. Two experimental protocols were followed: C21 was administered (0.03 mg/kg/day, ip) either immediately (prevention protocol, BCP) or after three days (treatment protocol, BCT) of bleomycin-instillation. Echocardiography, hemodynamic and Fulton’s index assessments were performed after two weeks of bleomycin-instillation. Lung tissue was processed for gene expression, hydroxyproline content (a marker of collagen deposition), and histological analysis. C21 treatment prevented as well as attenuated the progression of lung fibrosis, and accompanying PH. The beneficial effects of C21 were associated with decreased infiltration of macrophages in the lungs, reduced lung inflammation and diminished pulmonary collagen accumulation. Further, C21 treatment also improved pulmonary pressure, reduced muscularization of the pulmonary vessels and normalized cardiac function in both the experimental protocols. However, there were no major differences in any of the outcomes measured from the two experimental protocols. Collectively, our findings indicate that stimulation of the AT2 receptor by C21 attenuates bleomycin-induced lung injury and associated cardiopulmonary pathology, which needs to be further explored as a promising approach for the clinical treatment of IPF and Group III PH.